Determinant Factors Of Teacher Performance And Students’ Competency - Sambas Ali Muhidin (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2019)
This study aims to analysis the relationship between principal leadership, organizational climate, competency and motivation toward teacher performance and students’ competency. For the study, the verification survey research method was used, in the unit of analysis of vocational teachers in Business and Management Expertise in Bandung. The data analysis technique used is path analysis. The results showed that there was a positive and significant contribution of principals’ leadership, organizational climate, competence, and work motivation to teacher performance, both partially and simultaneously. Therefore, the conclusions of the study are the high or low teacher performance determined by the effectiveness of the leadership of the principal, the conduciveness of the school organizational climate, the high and low teacher competencies, and the high and low motivation of the teacher’s work.